Outros homens, outros tempos e outros lugares : os livros dos outros e os outros nos livros - Leite, Isabel Pereira (2015)
All human beings are different. Unique. Something always remains to prove that everyone is irreplaceable. Centuries of books, crossing worlds, have been touching mankind in both clear and unsuspected ways.One thing we can say for sure: writers and readers cannot live apart. Those who traveled in time and lived in unbelievable places, coming right from the writer's imagination, can easily be part of our lives. It is absolutely true that for a large variety of reasons, many times we feel such a perfect identification with some characters, that their existence becomes «real». Saint-John Perse, Italo Calvino, Roald Dahl, Nikos Kazantzákis and Victor Hugo, among uncountable names, gave us much of what we are today. But what do they search, undercovered, multiplying themselves in characters, some of them living forever in our memory? What do they look for? Is there a reason for their existence? What did Hermann Hesse and Romain Gary, for instance, think about happiness and love? Words, in our particular case written words, have been powerful enough to eliminate every obstacle, possessing our inner selves in ways far from consciousness. The reader becomes «the other». Inside and outside the book there are no differences.Who are we? Amazing, fantastic, terrifying, although nonexistent libraries, from more than a dozen novels, are the main theme of the present reflection. Because we believe that all words, all books, all libraries can be eternal - it depends on us wanting to become «the other» - there is no place for oblivion.